ESTROGEN IN THE TREATMENT OF DEPRESSION: A CASE REPORT - Kusuma, Putu Andrika (E-Jurnal Medika Udayana; vol 3 no 2 (2014):e-jurnal medika udayana)
Depression led to the decline quality of life. With more incidence in women due to hormonal cycle caused women more susceptible to depression. Hormone that fluctuates and holds a key role in brain and nerve cells is estrogen. Estrogen in premenopausal women already decreases. Treatment of depression in premenopausal women who go past the various considerations needs to consider the provision of hormonal therapy. In the case of patients treated with psychotherapy and pharmacotherapy in the form of 2 x 20 mg Fluoxetine by mouth and hormonal therapy in the form of 1 x 2 mg Estradiol. Feasibility study to evaluate the hormonal therapy contraindications such as breast cancer also needs to be done.
Keywords: estrogen, depression